How do weeds affect us all and what is the way-out? - S.M. Rezaul Karim (2013)
Weed means “a plant out of place” or “a plant that interferes with the management objectives of a given area of land at a given point in time”. A rice plant in a wheat field or a wheat plant in a rice field is weed. A plant of good pasture crop growing in a well-managed lawn is also a weed. Similarly, a plant of medicinal value growing unwontedly on the roof of a building is a weed. Weeds are pollutants to our environment. They appear attractive, desirable, or harmless, but later it can be toxic, painful, or injurious to humans, and may create associated water quality problems.